Pengaruh Perencanaan Pajak dan Relevansi Nilai Laba Terhadap Nilai Perusahaan dengan Kepemilikan Institusional sebagai Pemoderasi - Ira Alpina BR Surbakti; Nera Marinda Machdar (UNIVERSITAS KALBIS, 2022)
This study examines the effect of tax planning and the value relevance of earnings on firm value with institutional ownership as moderating. This study uses a sample of manufacturing companies listed on Indonesia Stock Exchange (IDX) in the range of 2013-2017. The research sample used was 51 companies with 255 observations. Data analysis used multiple regression analysis and Moderated Regression Analysis (MRA). The results of the study with multiple regression analysis show that tax planning does not have a significant effect on firm value, while the relevance of earnings values ​​has a significant effect on firm value. The analysis of the moderating variable with the MRA test shows that disclosure of institutional ownership is not able to moderate the relationship between tax planning to firm value, while disclosure of institutional ownership is able to moderate the relationship between the relevance of earnings value to firm value.